2018
DOI: 10.1038/s41598-018-30774-2
|View full text |Cite
|
Sign up to set email alerts
|

Urea influences amino acid turnover in bovine cumulus-oocyte complexes, cumulus cells and denuded oocytes, and affects in vitro fertilization outcome

Abstract: High-protein diets often lead to an increase in urea concentration in follicular fluid of dairy cows, which may reduce oocyte competence. In the present study, maturation media were supplemented with urea (0, 20, 40 mg/dl), and amino acids (AAs) turnover was evaluated in the 24-h spent media of specimens (cell types), bovine cumulus-oocyte complexes (COCs), cumulus cells (CCs), or denuded oocytes (DOs). The main effects of urea and cell type, and their interaction were significant on the individual turnover (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 59 publications
0
18
0
1
Order By: Relevance
“…Moreover, the depletion of AAs was the highest in urea-incubated COCs with greater depletion in non-cleaved COCs than in cleaved COCs using an individual-IVM culture. Recently, we observed a greater depletion of AAs and a decrease in oocyte competence in the presence of high urea levels in the group-IVM system 17 . Similarly, Hemmings et al reported that higher AA depletion is associated with a decrease in the developmental competence of oocytes in humans and bovines 18 , 19 .…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Moreover, the depletion of AAs was the highest in urea-incubated COCs with greater depletion in non-cleaved COCs than in cleaved COCs using an individual-IVM culture. Recently, we observed a greater depletion of AAs and a decrease in oocyte competence in the presence of high urea levels in the group-IVM system 17 . Similarly, Hemmings et al reported that higher AA depletion is associated with a decrease in the developmental competence of oocytes in humans and bovines 18 , 19 .…”
Section: Discussionmentioning
confidence: 88%
“…We have previously reported that high urea levels not only increased the percentage of oocyte degeneration, but also decreased the in vitro viability of CCs and oviduct epithelial cells 16,17,39 . In this study, the addition of urea to the maturation medium increased the percentage of oocyte degeneration by day 3 after insemination.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations